2022
DOI: 10.3390/antiox11061132
|View full text |Cite
|
Sign up to set email alerts
|

Is There an Optimal Combination of AREDS2 Antioxidants Zeaxanthin, Vitamin E and Vitamin C on Light-Induced Toxicity of Vitamin A Aldehyde to the Retina?

Abstract: Vitamins C and E and zeaxanthin are components of a supplement tested in a large clinical trial—Age-Related Eye Disease Study 2 (AREDS2)—and it has been demonstrated that they can inhibit the progression of age-related macular degeneration. The aim of this study was to determine the optimal combinations of these antioxidants to prevent the phototoxicity mediated by vitamin A aldehyde (ATR), which can accumulate in photoreceptor outer segments (POS) upon exposure to light. We used cultured retinal pigment epith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 94 publications
0
8
0
Order By: Relevance
“…It has been shown that about 15–25% of retinal carotenoids are present in POS [ 34 , 35 ]. Sommerburg et al determined the content of lutein and zeaxanthin in POS isolated from the entire human retina so their molar concentrations can be estimated as 1.01 µM for lutein and 0.47 µM for zeaxanthin [ 34 , 37 ]. It is reasonable to expect that in the macula, where the concentrations of these carotenoids in the RPE are several-fold greater than in the periphery and their concentrations in the inner retina of the central macula reach millimolar values, the concentrations of lutein and zeaxanthin in POS will be also greater than in the periphery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown that about 15–25% of retinal carotenoids are present in POS [ 34 , 35 ]. Sommerburg et al determined the content of lutein and zeaxanthin in POS isolated from the entire human retina so their molar concentrations can be estimated as 1.01 µM for lutein and 0.47 µM for zeaxanthin [ 34 , 37 ]. It is reasonable to expect that in the macula, where the concentrations of these carotenoids in the RPE are several-fold greater than in the periphery and their concentrations in the inner retina of the central macula reach millimolar values, the concentrations of lutein and zeaxanthin in POS will be also greater than in the periphery.…”
Section: Discussionmentioning
confidence: 99%
“…Based on data of Friedrichson et al, it has been determined that molar concentrations of vitamin E in the neural retina of the macular area and periphery are 46 and 77 µM, respectively [ 29 , 37 ]. Comparison of calculated effectiveness of retinol cation radicals scavenging clearly shows that, in comparison with lutein and zeaxanthin, α-tocopherol can provide only a minor contribution to the scavenging of the retinol cation radical in the macula but is similar or exceeds the contribution of these carotenoids in the periphery despite that the rate constant for scavenging of retinol cation radicals is 158 times greater for lutein than for α-tocopherol ( Table 3 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vitamin A or all-trans-retinal, which accumulates in the retina because of the absorption of light by visual pigments, is found in carrots, egg yolk, liver, and sweet potatoes [ 238 , 239 ]. Being a liposoluble vitamin, a balance in its intake is to be considered [ 239 ].…”
Section: Natural Antioxidants and Their Benefitsmentioning
confidence: 99%
“…6 In addition, the lysosomal degradation in the RPE can be hindered by oxidative damage to the phagocytosed material due to the photosensitizing properties of retinaldehydes. Following the photoexcitation of visual pigment, which is the first step leading to visual perception, the Schiff base linkage between the protein and the isomerized chromophore is hydrolyzed, resulting in a release of all-trans-retinaldehyde from the protein, opsin [88,[94][95][96][97][98]. The lysosomal degradation of the visual pigments can lead to the release of their intact chromophore, 11-cis-retinaldehyde.…”
Section: Oxidative Stress Lysosomal Dysfunction and Vitamin A Derivat...mentioning
confidence: 99%